The meaning of the UHECR Hot Spots - Fargion Daniele; Ucci Graziano; Oliva Pietro; Lucentini Pier Giorgio De Sanctis (EPJ Web of Conferences, 2015)
In this paper we review all the up-to-date Ultra High Energy Cosmic Ray (UHECR) events reported by AUGER, the Telescope Array (TA) and AGASA in common coordinate maps. We also confirm our earliest (2008–2013) model, where UHECRs mostly comprise light nuclei (namely He, Be, B), which explains the Virgo absence and confirms M82 as the main source for the Northern TA Hot Spot. Many more sources, such as NGC253 and several galactic sources, are possible candidates for most of the 376 UHECR events. Several correlated maps, already considered in recent years, are reported to show all the events, with their statistical correlation values.